2023
DOI: 10.1111/sum.12893
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, perceptions and utilizations of termite mounds in Cambodia

Abstract: In the Lower Mekong Basin, paddy fields often appear as mosaics, with soil mounds covered by trees or other plants in a spotty distribution. These soil mounds are commonly named termite 'lenticular mounds' because termite bioturbation is considered to be at their origin. Termite mounds host a large diversity of animals and plants, increasing landscape patchiness. Because the preservation of these islands of biodiversity is threatened by modern agricultural practices, the aim of this study was to quantify their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…A study in Cambodia found that soil mounds originated from termite bioturbation host abundant soil animals and plant species (see Figure 4). The mounds were widely used by local farmers to increase the fertility of their rice fields (Muon et al, 2023). A global meta‐analysis shows that the presence of earthworms in agroecosystem increased crop yield by 25% (Van Groenigen et al, 2014).…”
Section: Sustainable Plant Growth Soil Animal and Microbial Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…A study in Cambodia found that soil mounds originated from termite bioturbation host abundant soil animals and plant species (see Figure 4). The mounds were widely used by local farmers to increase the fertility of their rice fields (Muon et al, 2023). A global meta‐analysis shows that the presence of earthworms in agroecosystem increased crop yield by 25% (Van Groenigen et al, 2014).…”
Section: Sustainable Plant Growth Soil Animal and Microbial Diversitymentioning
confidence: 99%
“…Termite mounds in Lower Mekong Basin nested by abundant soil animals and plant species (Muon et al, 2023). …”
Section: Sustainable Plant Growth Soil Animal and Microbial Diversitymentioning
confidence: 99%
See 1 more Smart Citation